Archives as Information Infrastructure and Their Urgency Towards Research - L Nurdin (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2021)
This research was conducted to investigate archives as information infrastructure in research. This term is used because archives are seen as the primary source for research. Thus, it is very fundamental and urgent for researchers regarding the data to be used and their accuracy is reliable. The research used a qualitative descriptive method in the frame of a constructivist approach in reading the phenomena of UIN Sunan Kalijaga Archives. Data collection was carried out using three main techniques, namely interview, observation, and documentation. The results of the study found three important issues related to the existence of archives as information infrastructure on research, i.e. archives as a means of historical preservation, primary document, and research development capital. As a curator of history, it seems that its function is very important in historical research because its birth was not intended to produce historical materials, but was born by itself following the interaction of the people. As a primary document, archives are important because they were born simultaneously with events, not from the stories of social actors. As for the framework of research development capital, archives are a source that has a high degree of accuracy, so that its function in research is very important to produce qualified research.